New Strategies for Medium- and Large-Ring Lactone Synthesis - Zhao, Wanxiang; Sun, Jianwei (Synlett, 2014)
Efficient synthesis of medium- and large-ring lactones is an important topic in organic synthesis. Summarized here are the conventional approaches and two recently reported new strategies. The both new intermolecular reactions employ siloxy alkynes as the key reaction partner. Enabled by the design of new (1,6)-amphoteric molecules and unprecedented ring expansion of fused oxetenium species, the two processes not only provide new solutions to medium- and large-ring lactone synthesis, but also overcome the drawbacks of traditional intramolecular cyclization strategies that typically require high dilution or slow addition.
Keywords: alkynes; lactones; cyclization; ring opening; catalysis